Conducting resisted sled sprint load-velocity profiling in female rugby league athletes—reliability and sled load using velocity decrement - Martin, A.; Duhig, S.; Bourne, M.; Minahan, C.; Bellinger, P. (The Journal of Strength and Conditioning Research, 2025)
Resisted sled sprinting (RSS) is a training method used to improve short distance sprinting performance. Previous research has individualized sled loads using a 50% velocity decrement (VDEC) to achieve an optimum load (LOPT percentage of body mass [%BM]) targeting maximum power output (Pmax [W·kg-1]). However, RSS load-velocity (L-v) profiling to determine a 50% VDEC has predominantly been conducted in male cohorts. Sampling exclusively female athletes, the aims of this study are to (a) determine the interday reliability of the L-v slope and LOPT at 50% VDEC and (b) provide L-v profiling protocol recommendations for sled loading and relative trial distances. Sixteen female rugby league athletes (age: 21.29 ± 7.09 years; BM: 74.94 ± 11.42 kg; height: 1.71 ± 0.05 m) completed a minimum of 2 familiarization sessions followed by L-v testing on 2 days 7 days apart. Using the coefficient of variance (CV), an acceptable absolute interday reliability of LOPT (%BM) was found when derived from trial peak velocity (Vpeak) and trial average velocity of the maximum velocity plateau (VAVGMVP) (CV = 1.82-4.39%, CV = 1.33-5.09%). Poor to excellent or good relative reliability was determined for Vpeak (intraclass correlation coefficient [ICC3,1] = 0.73 [0.26 to 0.90]) and VAVGMVP (ICC3,1 = 0.62 [-0.12 to 0.87]). Using Vpeak (m·s-1) and VAVGMVP (m·s-1) methods, the %BM required to induce a 50% VDEC ranged from ˜59 to 72% BM and from ˜58 to 71% BM, respectively. Resisted sled sprinting L-v profiling load protocols are recommended to range between 25 and 100% BM to achieve a reliable L-v slope, while relative trial distances should range between 10 and 30 m in female field sport athletes.